(untitled) (Conference Zone, 2022)
Currently, the import of large quantities of pasta and confectionery products from foreign countries, which are necessary for the needs of the population, affects the state budget. The quality of grain grown often does not fully meet the requirements of the bakery, pasta and confectionery industries. One of the most pressing issues in agriculture is the creation of new high-yielding, fast-maturing, dormant and disease-resistant varieties in the cultivation of durum wheat. The article is based on the study of new forms of hybrid lines to create early-maturing and yielding varieties of durum wheat.